Structure and composition of ferromanganese-phosphate nodules from the Black Sea. - Baturin, Gleb N; Gorshkov, Anatoly I; Magazina, Larissa O; Bogdanova, Olga Yu (PANGAEA, 2002)
Ferruginate shells and tubular worm burrows from the oxygenated zone of the Black Sea (Kalamit Bay and Danube River mouth) are studied by transmission and scanning electron microscopy combined with analyses of elemental composition. Iron and manganese oxyhydroxide nodules considered here are enriched in phosphorus. They contain variable amounts of terrigenous and biogenic material derived from host sediments. Oxyhydroxides are mainly characterized by colloform structure, whereas globular and crystalline structures are less common. The dominating iron phase is represented by ferroxyhite and protoferroxyhite, whereas the manganese phase is composed of Fe-free vernadite. Concentrations of Mn, As, and Mo are 12-18 times higher relative to sediments, while concentrations of Fe, P, Ni, and Co increase 5-7 times during nodule formation.
Chemical composition of ferromanganese nodules from the Black Sea
Keywords: Archive of Ocean Data; ARCOD; Black Sea; MULT; Vy8-798; Vy8-800; Vy8-802; Vy8-848